Is the flow‐aligned component of IMF really able to impact the magnetic field structure of Venusian magnetotail?. Issue 11 (21st November 2016) - Rong, Z. J.; Stenberg, G.; Wei, Y.; Chai, L. H.; Futaana, Y.; Barabash, S.; Wan, W. X.; Shen, C.
Abstract: An earlier statistical survey suggested that the flow‐aligned component of upstream interplanetary magnetic field (IMF) may play an important role in controlling the lobe asymmetries of the Venusian magnetotail. The tail current sheet would be displaced and the magnetic field configuration would show asymmetries with respect to the current sheet. The asymmetries are expected to be more evident when the flow‐aligned component becomes dominant. Here with carefully selected cases as well as a statistical study based on Venus Express observations in the near‐Venus tail, we show that the lobe asymmetries of the magnetic field as well as the displacement of the current sheet are common characteristics of the Venusian magnetotail. However, the asymmetries and the displacement of the current sheet do not show a significant dependence on the flow‐aligned component of the IMF. Our results suggest that the flow‐aligned component of IMF cannot penetrate into the near magnetotail to impact the magnetic field structure. Key Points: IMF Bx cannot significantly displace the current sheet of Venusian magnetotail IMF Bx cannot significantly impact the magnetic field structure over current sheet It implies IMF flow‐aligned component cannot penetrate into near‐Venus tail